Lisa — La jeune esclave indienne/A Young Indian Slave - Paradis, Roger (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1992)
Lisa — la jeune esclave indienne is a ballad about a young Indian slave girl who pleads for her liberty from the auction block of a slave market. This study is a comparative and critical analysis of eight variants of the song, recorded from the State of Maine to the Canadian Province of Saskatchewan. It also examines the poetic structure, morphology and peregrination of the song against the background of Indian slavery in North and South America.